2020
DOI: 10.2478/amb-2020-0043
|View full text |Cite
|
Sign up to set email alerts
|

Outcome After Azacitidine Treatment in Patients with High-Risk Myeolodysplastic Syndrome, Chronic Myelomonocytic Leukemia Type 2 and Acute Myeloid Leukemia – A Single Center Experience (Preliminary Data)

Abstract: Introduction: Hypomethylating agents have become a standard therapy for certain myeloid malignancies.Aim: The aim of this preliminary study was to assess efficacy and safety of azacitidine in patients with myelodysplas tic syndromes (MDS), chronic myelomonocytic leukemia with 10-29% blasts (CMML-2) and acute myeloid leukemia (AML) treated in a single center.Material and Methods: Twenty-six (69% male and 31% female, median age 67.8 years) patients (MDS, = 15; CMML-2, n = 2; AML, n = 9) treated with azacytidine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…The rates of thrombocytopenia (18.5%) and anemia (only 7%) were lower. These data are consistent with the fi ndings of other authors (Varbanova et al) who reported the most frequent adverse events being neutropenia 38.5%, followed by anemia 15.4% and thrombocytopenia 11.5% [6].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The rates of thrombocytopenia (18.5%) and anemia (only 7%) were lower. These data are consistent with the fi ndings of other authors (Varbanova et al) who reported the most frequent adverse events being neutropenia 38.5%, followed by anemia 15.4% and thrombocytopenia 11.5% [6].…”
Section: Discussionsupporting
confidence: 93%
“…Yet in our patients, karyotype 46,XX,del(5q) or 46,XY,del(5q) was not detected. Nevertheless, Varbanova et al reported del(5q) in one patient with a good prognostic risk [6]. We report additional chromosome 8 and a partial deletion of chromosome 7 (deletion 7q) in two separate cases (Table 2).…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation